2014
DOI: 10.1063/1.4871522
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic perfusion platform for cultivation and screening study of motile microalgal cells

Abstract: Systematic screening of algal cells is getting huge interest due to their capability of producing lipid-based biodiesel. Here, we introduce a new microfluidic platform composed of an array of perfusion chambers designed for long-term cultivation and preliminary screening of motile microalgal cells through loading and releasing of cells to and from the chambers. The chemical environment in each perfusion chamber was independently controlled for 5 days. The effect of nitrogen-depletion on the lipid production, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…28,29 Recent microfluidic advances directed at algal cultures include microfluidic reactors that study microalgal growth in static droplet arrays 30 and multiplexed chemical environments. 31,32 Recently, Shih et al 24 demonstrated how the effect of irradiance conditions on the growth of algae could be studied within a digital microfluidic platform. Eight cultures were studied simultaneously, each grown using a separate LED light source.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Recent microfluidic advances directed at algal cultures include microfluidic reactors that study microalgal growth in static droplet arrays 30 and multiplexed chemical environments. 31,32 Recently, Shih et al 24 demonstrated how the effect of irradiance conditions on the growth of algae could be studied within a digital microfluidic platform. Eight cultures were studied simultaneously, each grown using a separate LED light source.…”
Section: Introductionmentioning
confidence: 99%
“…Insight into factors that affect and limit single-cell growth and behaviour might be applied to scale-up the growth of algae, both in flask culture in the laboratory, and at industrial scale for algal biotechnology. In fact, the behaviour of individual trapped microalgal cells has been studied using several different microfluidic approaches, trapping small numbers of cells in a range of devices, including microfluidic chambers [53][54][55][56][57][58][59][60] and capsules [61,62]. These are summarised in Table 1. Pan et al developed an experimental platform in which single microalgal cells were encapsulated into droplets and their growth tracked [51].…”
Section: Monitoring Individual Microalgal Cells Held In Dropletsmentioning
confidence: 99%
“…Microalgae can produce high energy biochemicals through photosynthesis using sunlight, H 2 O, and CO 2 (Eu et al, 2014). Microalgae have therefore been recently proposed as a renewable energy alternative for the production of biofuels to meet the world's growing demand for fuels (Eu et al, 2014;Holcomb et al, 2011;Park et al, 2013).…”
Section: Effect Of Physical Stress On Morphology and Function Of Micrmentioning
confidence: 99%
“…Microalgae are photoautotrophic organisms and are generally more efficient converters of solar energy compared to terrestrial plants (Eu et al, 2014;Holcomb et al, 2011;Park et al, 2013). Microalgae can produce high energy biochemicals through photosynthesis using sunlight, H 2 O, and CO 2 (Eu et al, 2014).…”
Section: Effect Of Physical Stress On Morphology and Function Of Micrmentioning
confidence: 99%
See 1 more Smart Citation